Multimodal dataset of real-time 2D and static 3D MRI of healthy French speakers - Karyna Isaieva (Nature Portfolio, 2021)
Measurement(s) Vocal tract images • Speech Technology Type(s) Magnetic Resonance Imaging • Microphone Device Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.16404453